2012
DOI: 10.1111/gfs.12027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spatial heterogeneity of plant species on herbage productivity, herbage quality and ewe and lamb performance of continuously stocked, perennial ryegrass–white clover swards

Abstract: The benefits of white clover (Trifolium repens L.) in pastures are widely recognized. However, white clover is perceived as being unreliable due to its typically low content and spatial and temporal variability in mixed (grass‐legume) pastures. One solution to increase the clover proportion and quality of herbage available to grazing animals may be to spatially separate clover from grass within the same field. In a field experiment, perennial ryegrass (Lolium perenne L.) and white clover were sown as a mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…() for weaned lambs grazing intensive irrigated lamb finishing systems on perennial ryegrass‐white clover pastures in New Zealand, and the 176 to 193 g per head d −1 for suckling twin lambs on perennial ryegrass‐white clover pastures in southeast England reported by Sharp et al . (). They also compare favourably with the high pre‐weaning twin lamb growth rates of 407 g per head d −1 reported by Muir et al .…”
Section: Discussionmentioning
confidence: 97%
“…() for weaned lambs grazing intensive irrigated lamb finishing systems on perennial ryegrass‐white clover pastures in New Zealand, and the 176 to 193 g per head d −1 for suckling twin lambs on perennial ryegrass‐white clover pastures in southeast England reported by Sharp et al . (). They also compare favourably with the high pre‐weaning twin lamb growth rates of 407 g per head d −1 reported by Muir et al .…”
Section: Discussionmentioning
confidence: 97%
“…In the other spatially separated treatments, the increased time taken for grass to invade the larger clover monocultures allowed the pasture to maintain a high clover content. While this cannot be supported by long-term experimental evidence, short-term studies show that spatial separation increases the clover content (18–30% in the spatially separated treatments v. 9% in the conventional mixture on a DM basis) and production (average over the growing season of 3 years 2881–3466 kg DM/ha in the spatially separated treatments v. 1470 kg DM/ha in the conventional mixture) at the field scale (Sharp et al 2012 a , b ). Pastures tend to deteriorate in productivity though time as less productive weed species, such as Poa spp.…”
Section: Discussionmentioning
confidence: 99%
“…While this model did not include any aspect of selective grazing, selective grazing can alter the competitive interactions between plant species and may lead to species coexistence, which in the absence of grazing may not occur. In studies using monocultures of differing sizes, evidence of preference is observed at all scales, but extinction of a particular plant species is not observed (Parsons et al 1994; Sharp et al 2012 a , b ). Therefore, in the short to medium term, spatial separation can result in an increase in the size and frequency of clover-rich patches, which could potentially have important implications for animal grazing behaviour and production.…”
Section: Discussionmentioning
confidence: 99%